Comparison of Antimicrobial Activity against Porphyromonas gingivalis between Advanced Platelet-Rich Fibrin and Injectable Platelet-Rich Fibrin - Thuy Anh Vu Pham (International Journal of Biomaterials, 2023)
Platelet-rich fibrin (PRF) obtained via low-speed centrifugation has antimicrobial properties. This study was conducted to evaluate the effectiveness of advanced platelet-rich fibrin plus (A-PRF+) and injectable platelet-rich fibrin (I-PRF), obtained from patients with different periodontal states, against Porphyromonas gingivalis. A-PRF+ and I-PRF samples were obtained from venous blood of 60 subjects divided equally into three groups: periodontitis, gingivitis, and healthy gingiva groups. The antibacterial experiments evaluated biofilm inhibition, mature biofilm impact, and time-kill kinetics. The percent reduction in biofilm-growing and mature biofilm bacteria ranged from 39% to 49% and 3% to 7%, respectively. In the time-kill kinetics assay, PRF from the periodontitis group was more effective as an antimicrobial than that from the gingivitis and healthy gingiva group (p<0.001); I-PRF was more effective than A-PRF+ (p<0.05) and both of them showed peak antibacterial activity after 12 h of exposure. Both A-PRF+ and I-PRF exhibited antibacterial properties against P. gingivalis, but I-PRF appeared to be more effective. The PRF obtained from the different groups appeared to have different degrees of antimicrobial efficacy.